Some personality dimensions in the academic achievement of the students of the Philippine Science High School - Abellera, Lourdes Cabrera 1948- (s.n.], 1974)
This study looked into certain personality variables as they relate to the academic achievement of a selected group of students - the sophomore, junior and senior students of the Philippine Science High School. It analyzed the results on the High School Personality Questionnaire, particularly the scores on the factors under consideration - extraversion, anxiety, and neurotic trend- by year level including the freshmen.